PKM: MENINGKATKAN LITERASI MELALUI STRATEGI BINCANG NUMERASI BAGI SEKOLAH YANG NILAI NUMERASINYA MASIH RENDAH DI KABUPATEN BADUNG - I Dewa Putu Juwana; I Ketut Muada; Ni Made Pira Erawati; Dewa Ayu Widiasri; I Ketut Lanus; Ni Wayan Dian Permana Dewi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This Community Service (PkM) activity aims to improve the numeracy literacy of elementary school students who still show low achievement in numeracy assessments, especially in Badung Regency. One of the strategies implemented is "Bincang Numerasi", which is an interactive learning approach that invites students to discuss, analyze, and relate mathematical concepts to everyday life. The method of implementing the activity includes training and mentoring teachers in compiling and implementing numeracy teaching modules based on the Merdeka Curriculum, integrating technology in learning, and strengthening the management of digital libraries to support access to numeracy teaching materials. In addition, this strategy also involves the active role of parents and the community in supporting the habituation of numeracy discussions in the home and community environment. The results of the activity show an increase in students' numeracy abilities, an increase in teacher competence in compiling and implementing contextual learning, and the formation of a numeracy learning culture in partner schools. The implementation of the "Bincang Numerasi" strategy also has a positive impact on the management of learning resources and digital libraries in schools. Thus, this strategy is effectively implemented as a solution to increase numeracy literacy in elementary schools, especially those facing the challenge of low numeracy achievement.